Maximilian Hell (1720-92) and the Ends of Jesuit Science in Enlightenment Europe - Aspaas, Per Pippin (Jesuit Studies, 2019)
The Viennese Jesuit astronomer Maximilian Hell was a nodal figure in the eighteenth-century circulation of knowledge. This study of his career sheds light on the Enlightenment, Catholicism, reform in the Habsburg monarchy, and the cultivation of science in the Republic of Letters. Readership: Anyone interested in eighteenth-century Central Europe and Scandinavia, in the production and circulation of knowledge in the Enlightenment, in enlightened absolutism, in Catholicism and the Society of Jesus in the eighteenth century, in the history of astronomy and related subjects, and the history of comparative linguistics and its ideological implications.